Gas Price Cap, Electricity Market and Macro Effects in Germany and the EU - Werner Röger; Paul J. J. Welfens (Wirtschaftsdienst)
Abstract Since late summer 2022, policymakers in Germany and many other European Union countries have increasingly discussed imposing a gas price cap and introducing transfer payments to private households. Against the background of current policy proposals with a rather limited analytical foundation for gas price caps, the following model based analysis with a special emphasis on a gas price cap only in the electricity market — combined with certain transfers — is optimal from a economic perspective.